Trends in Physical Activity Research on Tobacco And/Or Alcohol: A Bibliometric Analysis - De Moraes-Ferrari, G; Castillo-Paredes, A (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Physical activity allows the enjoyment of personal health benefits in those who practice it, including the possibility of modifying behavioral risk factors such as tobacco and alcohol consumption. These risk factors are responsible for the development of non-communicable diseases, which are preventable and controllable. The scientific field on this object of study has grown in recent years. The main objective of this study was to perform a scientific mapping to explore the trend of annual publications, and to analyze and identify the thematic categories, the authors, countries and journals with the highest number of papers, the most referenced papers and authors, and the most used keywords in research related to physical activity and tobacco and/or alcohol consumption. Methods: Through a bibliometric analysis based on traditional bibliometric laws on the scientific documentation related to the subject and indexed in the Main Collection of the Web of Science. The DeSolla Price Law was used to analyze the trend of annual publications, using the coefficient of determination R2. Lotka’s law was applied to identify prolific authors, Bradford’s law to highlight the most frequent publication sources, the h-index to identify the most cited articles and Zipf’s law to highlight the keywords most used in research. Results: A total of 538 documents were analyzed. The trend followed by annual publications is in an exponential growth phase. Adrian Taylor and Michael Ussher were identified as prolific authors. USA and Preventive Medicine were the country and journal with the highest number of publications. The most frequently used words were physical activity, smoking, exercise, alcohol, obesity, and smoking cessation. Conclusions: This bibliometric review identified an exponential growth from 1994 to date of research related to physical activity and tobacco and/or alcohol consumption. It allowed us to identify trends and guide the development of future research in these or new related areas. © 2025 by the authors.